Soldier dogs : the untold story of America's canine heroes - Goodavage, Maria, 1962- (Dutton, 2012)
A dog's natural intelligence, physical abilities, and pure loyalty contribute more to our military efforts than ever before. You don't have to be a dog lover to be fascinated by the idea that a dog, the cousin of that furry guy begging for scraps under your table, could be one of the heroes who helped execute the most vital and high-tech military mission of the new millennium. Now the author, an editor and featured writer for one of the world's most widely read dog blogs, tells heartwarming stories of modern soldier dogs and the amazing bonds that develop between them and their handlers. She talks to leading dog-cognition experts about why dogs like nothing more than to be on a mission with a handler they trust, no matter how deadly the IEDs they are sniffing, nor how far they must parachute or rappel from aircraft into enemy territory. "